West Palaearctic taxa formerly connected to the ‘old’ genus Atritomus Reitter, 1877 (Coleoptera, Mycetophagidae): taxonomy, distribution, and description of a new genus - Biscaccianti, Alessandro B.; Esser, Jens; Cuoco, Silvio; Giuliano Grimaldi, Enrica; Audisio, Paolo A. (European Journal of Taxonomy, 2022)
The present study aims to resolve the taxonomic confusion involving several taxa within Mycetophagidae Leach, 1815, originating from the introduction of the genus Atritomus Reitter, 1877, and then by its subsequent controversial interpretation. A detailed overview of the taxonomic and nomenclatural history of the taxa previously linked to Atritomus is provided. The authors propose the introduction of Stereophilus Biscaccianti, Audisio & Esser gen. nov. for Atritomus filicornis Reitter, 1887, and the restoration of Entoxylon Ancey, 1869 at the genus rank, together with some rectifications regarding the authorship and the date of publication of both Entoxylon and its type species, E. abeillei Ancey, 1869. Moreover, the Ethiopian species Atritomus vicinus Grouvelle, 1908 is herein transferred to the genus Typhaeola Ganglbauer, 1899 based on the examination of the holotype. The following new combinations are proposed: Entoxylon baudii (Seidlitz, 1889) comb. nov. (from Esarcus Reiche, 1864), Entoxylon besucheti (Dajoz, 1964) comb. nov. (from Esarcus subg. Entoxylon), Entoxylon franzi (Dajoz, 1964) comb. nov. (from Esarcus subg. Entoxylon), Entoxylon inexpectatus (Dajoz, 1964) comb. nov. (from Esarcus subg. Entoxylon), Entoxylon martini (Reitter, 1887) comb. nov. (from Esarcus), Stereophilus filicornis (Reitter, 1887) gen. et comb. nov. (from Atritomus), Typhaeola vicina (Grouvelle, 1908) comb. nov. (from Atritomus).